PENERAPAN ASPEK RITMIS DALAM MEMBANGUN FILM “EGO” DENGAN GENRE DRAMA KOMEDI - I Made Angga Wicaksana Yasa; Ni Kadek Dwiyani; I Made Denny Chrisna Putra (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
The editing aspect is a technique that is well known in the film world, especially editing. At the beginning of the development of film, filmmakers were well aware of the powerful influence of the editing aspect in manipulating time and space. Editors can choose one of the four aspects of editing, one of which is the rhythmic aspect which will be applied to the making of a film entitled